A Novel Multiple High-Pressure Water-Jets Assisted Cutting Head in Rock Fragmentation - Jiang, Hongxiang; Yang, Pei; Du, Changlong (Recent Patents on Mechanical Engineering, 2017)
Background: Hard rock fragmentation is still an issue to be solved in coal mining, roadway construction, oil drilling, etc. Development of new methods and technologies are desired to overcome the existing problems of hard rock fragmentation, such as low efficiency, severe wear of conical pick, high cutting dust concentration. Objective: A novel multiple high-pressure water-jets assisted cutting head is developed in this paper, whose aim is to improve the hard rock fragmentation performance by the cutting head efficiently. Methods: Patent of the developed high-pressure water-jets assisted cutting head integrates several high-pressure water-jets onto the carbide tip of conical picks, and the tension action due to water pressure in the rock crack is expected to promote the rock fracture by the mechanical tool. Results: According to the theoretical model, the reduction ratio of hydraulic pick force is determined by the rock fracture toughness under Mode I fracture, the water pressure in rock crack, the crack length, the crack length acting by water pressure, etc. The reduction ratio of cutting torque is over 30% when the rock compressive strength is lower than the water-jets pressure. Conclusion: The ratio between the rock compressive strength and water pressure can be regarded as an index to estimate the rock fragmentation performance using the developed cutting head, and it can be used to determine the water-jet pressure according to the rock compressive strength.
Keywords: Cutting head